Estudo comparativo do efeito da temperatura na estabilidade e espectros de bioluminescência das luciferases de Phrixotrix hirtus e outros besouros bioluminescentes - Oliveira, Gabriela de (2019)
Firefly luciferases have been extensively used as bioanalytical reagents and their cDNAs as reporter genes and bioimaging biosensors. Luciferases of fireflies, “rail-road” worm and "tec-tec" beetles, have different characteristics of thermostability, kinetics and spectrum of bioluminescence, being able to offer alternatives to increase the applications of these enzymes. However, most of these enzymes are unstable at temperatures above 30 ° C, and firefly luciferases exhibit bioluminescence spectra sensitive to temperature. In this thesis, we conducted an extensive study of the effect of temperature on the stability and bioluminescence spectra of recombinant luciferases from Brazilian bioluminescent beetles, and we used site-directed mutagenesis to increase the thermostability of red-light-emitting luciferase from Phrixotrix hirtus. The most thermostable luciferases were the ones that emitted the most shifted light to the blue within each family: that of the Elateridae Pyrearinus termitilluminans (534 nm), that of the Phengodidae Phrixotrix vivianii (546 nm) and that of the Lampyridae Amydetes vivianii (538 nm), confirming that emitting luciferases in the region from green to blue are more stable. All the pH-sensitive luciferases of fireflies studied here presented sensitivity of the bioluminescence spectrum to temperature. The luciferases with the most displaced bioluminescence spectrum for blue were also less temperature sensitive in the following order: Amydetes <Cratomorphus <Photinus <Macrolampis. It was also possible to verify the existence of a linear relationship between temperature and light intensity ratio in the green and red regions, which allow quantifying raciometrically the temperature using these luciferases. Finally, P. hirtus red light-emitting luciferase was resistant to stabilization by site-directed mutagenesis, only N351E and R353E showed slightly higher thermostability than the wild-type enzyme, preserving the same bioluminescence spectrum. The results suggest that this red light-emitting luciferase is very flexible, requiring considerable engineering to stabilize it.